Ekostruktur Vegetasi di Sekitar Ramin (Gonystylus bancanus) pada Kawasan Laboratorium Alam Lahan Gambut Universitas Palangka Raya: The Structure of Vegetation Communities Surrounding Ramin (Gonystylus bancanus) Trees in the Natural Laboratory Area of Palangka Raya University Peatland - Setiarno; Nababan, Suzet Rotua Tanya; Hidayat, Nisfiatul; Rotinsulu, Johanna Maria; Junaedi, Ajun (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2024)
The purpose of this study is to examine the vegetation's composition and ecostructure surrounding the Ramin tree (Gonystylus bancanus) in the University of Palangka Raya's Natural Laboratory of Peatlands. Vegetation data collection was carried out using the quadrat plot technique, with the plot placement applied through purposive systematic sampling. The Importance Value Index (IVI), species dominance index, diversity index, and evenness index were employed to examine the data from this research graphic using Microsoft Excel. In this study, 47 different plant species from different communities were identified and divided into 38 genera and 27 families (trees, poles, saplings and seedlings). The greatest number of species were found in the groups Myrtaceae and Dipterocarpaceae. There are no dominant species in the area with Nyatoh, Jambu-jambu, and Mangkinang nearly always occupy the five dominant species ranks from seedling to tree level at all peat thickness levels. While the species evenness index in all plant communities and the level of peat thickness are in the high/abundance category of almost evenly (E = 0.76 – 0.95), the majority of species diversity index (Shannon-Wiener value) in the research plots are classified as high (H'>3), indicating that the condition of the forest ecosystem at that location is relatively stable. Keywords: ecostructure, natural laboratory, peatlands, Ramin tree, vegetation